(untitled) (El-Wahat Journal for Research and Studies, 2021)
Judging The Validity Or Corruption Of Financial Treatment Is One Of The Most Important Concerns Of Scientists In The Old And Recent Past; Therefore, One Of The Most Important Tools Of Projection And Measurement Is The Knowledge Of The Origins Of Corruption, Its Causes And The Range Of Legitimate Purposes And Objectives To Which The Prohibition Was Made; It Is The Best Way To Learn About The Legitimate Governance Of The Decade. The Concept Of Corruption, Although It Is Intended To Vary Between The Public And Hanafi Scholars In Financial Transactions, Leads To A Single Fact; Financial Contracts, Whether Or Not They Are Said To Be Corrupt Or Void, Do Not Benefit The Legitimate Intent And Are Irrelevant; The Causes Of Corruption Are Three Types: Origins, General Reasons And Special Reasons, Which Are The Object The Research Mechanisms Highlight The General Origins And Reasons And The Intent Of The Sharia To Discourage Them And Then Drop Them On Some Models Of Recent New Contracts. Thus, The Assets To Which The Prohibition Is Attached And Which Have A General Effect In The Three Or More Contracts Are: Gharar, RIBA And The Sales Of The Conditions, And The General Reasons Are The Fact That One Of The Two Things Is Achieved If They Have A General Influence Or The Prohibition Of The Two: Prohibition Of The Eye And Coercion, And Others Is A Special Reason. Keywords: Corruption-Origins-Causes-Financial Transactions-A Spoiler Clause.